A Biomechanical Evaluation of All-Inside 2-Stitch Meniscal Repair Devices With Matched Inside-Out Suture Repair. (January 2014) - Ramappa, Arun J.; Chen, Alvin; Hertz, Benjamin; Wexler, Michael; Grimaldi Bournissaint, Leandro; DeAngelis, Joseph P.; Nazarian, Ara
Background: Many all-inside suture-based devices are currently available, including the Meniscal Cinch, FasT-Fix, Ultra FasT-Fix, RapidLoc, MaxFire, and CrossFix System. These different devices have been compared in various configurations, but to our knowledge, the Sequent meniscal repair device, which applies running sutures, has not been compared with the Ultra FasT-Fix, nor has it been compared with its suture, No. 0 Hi-Fi, using an inside-out repair technique. Purpose: To assess the quality of the meniscal repair, all new devices should be compared with the gold standard: the inside-out repair. To that end, this study aims to compare the biomechanical characteristics of running sutures delivered by the Sequent meniscal repair device with 2 vertical mattress sutures applied using the Ultra FasT-Fix device and with 2 vertical mattress sutures using an inside-out repair technique with No. 0 Hi-Fi suture. Study Design: Controlled laboratory study. Methods: Paired (medial and lateral), fresh-frozen porcine menisci were randomly assigned to 1 of 3 groups: Sequent (n = 17), Ultra FasT-Fix (n = 19), and No. 0 Hi-Fi inside-out repair (n = 20). Bucket-handle tears were created in all menisci and were subjected to repair according to their grouping. Once repaired, the specimens were subjected to cyclic loading (100, 300, and 500 cycles), followed by loading to failure. Results: The Sequent and Ultra FasT-Fix device repairs and the suture repair exhibited low initial displacements. The Sequent meniscal repair device demonstrated the lowest displacement in response to cyclic loading. No. 0 Hi-Fi suture yielded the highest load to failure. Conclusion: With the development of the next generation of all-inside meniscal repair devices, surgeons may use these findings to select the method best suited for their patients. Clinical Relevance: The Sequent meniscal repair device displays the least amount of displacement during cyclic loading but has a similar failure load to other devices.